Pengaruh Lokasi dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Jasa Pengiriman J & T di Muara Bulian - M Aziz Mukhlis (Ekonomis: Journal of Economics and Business, 2019)
Bussiness world competition currently is more progressively tight. It is also perceived by  services J & T In muara bulian. J & T is demanded to understand about the factors that can influence their customer’s satisfaction. J & T have to make some improvement and innovation that can increasing their customer’s satisfaction. The research aims to analyze how the influence of service quality, and location toward customer satisfaction. Sample of the research is 81 customer and then an analysis is performed toward the obtained data by using data analysis quantitatively and qualitatively. Quantitatively analysis includes: validity and realibility test, classical assumption test, multiple regression analysis and hypothesis test through t and F test, and determination coefficient analysis (R²). Qualitative analysis is an interpretation of the obtained data within research and the result of data processing has been implemented by providing information and explanation. Data has complied validity, realibility and classical test is processed, so that those are resulting regression equation as follows: Where, Y = a + b1 X1 + b2 X2 Customer Satisfaction (Y), Service Quality variable (X1), service qualitu variable (X2), and Location variable (X3). Hyphothesis test uses t test demonstrates that the three of examined independent variables is proved significantly have a partially effect on dependent variable of Customer Satisfaction. Then, follow the F test can be recognized that the three of examined independent variables has a simultaneously effect on dependent variable of Customer Satisfaction